Incidencia y conocimientos del síndrome dismenorreico en las alumnas de los Terceros Años de Bachillerato del Instituto Superior Tecnológico Daniel Álvarez Burneo de la Ciudad de Loja del período lectivo 2011 - 2012. - Alejo Rojas, Lizette Paola (2013)
Dysmenorrhea syndrome is a very common but little known that involves a group of symptoms, particularly pelvic pain, which responds to different, causes genital or extra- genital. Its intensity varies from simple discomfort to pain bearable violent, accompanied by an entourage of conditions that force women to change their lifestyle or bedridden. It is very common; occurring mainly in young women, for their high prevalence rate could be considered a public health problem. However, not yet effective solution raised the women often resort to self-medication only to treat it. In Latin America, Ecuador and especially in our province there is a high number of women with undiagnosed dismenorreico syndrome, for these reasons, the objective of this research was to determine the incidence and knowledge about this syndrome in the students of the third year of baccalaureate Higher Technological Institute “Daniel Alvarez Burneo". The present study is descriptive, prospective, cross-sectional surveys conducted over 132 randomly selected young. The 88% of respondents of discomfort during menstruation, 20% to come to the doctor for treatment, 70% self-medicate, and 96 % have no knowledge of this syndrome. Using the information collected is concluded that there is a high incidence of dismenorreico syndrome in the study group, high rate of self-medication, factors that contribute to appearance and low level of knowledge of it, so that this group also requested they provide more information on the subject. Keywords: Dysmenorrhea syndrome, women, knowledge, self-medication